2018
DOI: 10.1128/aac.01832-17
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Mediated Induction of Dispersal in Pseudomonas aeruginosa Biofilms Is Inhibited by Flavohemoglobin Production and Is Enhanced by Imidazole

Abstract: The biological signal molecule nitric oxide (NO) was found to induce biofilm dispersal across a range of bacterial species, which led to its consideration for therapeutic strategies to treat biofilms and biofilm-related infections. However, biofilms are often not completely dispersed after exposure to NO. To better understand this phenomenon, we investigated the response of biofilm cells to successive NO treatments. When biofilms were first pretreated with a low, noneffective dose of NO, a second dose of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 85 publications
(85 reference statements)
1
27
0
Order By: Relevance
“…Direct usage of gaseous NO also led to the dispersal of Staphylococcus aureus, Acinetobacter baumannii and Nitrosomonas europaea (Sulemankhil et al 2012 ; Schmidt et al 2004 ). SNAP and GSNO were reported to decrease P. aeruginosa biofilms although less effectively than SNP (Barraud et al 2006 ), while MAHMA NONOate, PROLI NONOate and Spermine NONOate exhibited higher performance against P. aeruginosa biofilms at 20 μM, 40 μM, and 100 μM respectively (Barnes et al 2013 ; Barnes et al 2015 ; Zhu et al 2018 ). However, the half-lives of MAHMA NONOate and PROLI NONOate are 1 min and 1.8 s at 37° C , respectively, limiting their applications under many circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct usage of gaseous NO also led to the dispersal of Staphylococcus aureus, Acinetobacter baumannii and Nitrosomonas europaea (Sulemankhil et al 2012 ; Schmidt et al 2004 ). SNAP and GSNO were reported to decrease P. aeruginosa biofilms although less effectively than SNP (Barraud et al 2006 ), while MAHMA NONOate, PROLI NONOate and Spermine NONOate exhibited higher performance against P. aeruginosa biofilms at 20 μM, 40 μM, and 100 μM respectively (Barnes et al 2013 ; Barnes et al 2015 ; Zhu et al 2018 ). However, the half-lives of MAHMA NONOate and PROLI NONOate are 1 min and 1.8 s at 37° C , respectively, limiting their applications under many circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Along with these, many studies were also carried out to explore novel methods for NO delivery, such as incorporating NO donors into nanoparticles and polymer coating (Sadrearhami et al 2017 ; Duong et al 2014a ; Nablo and Schoenfisch 2003 ; Nablo et al 2005 ). However, more often than not these studies tested different concentrations of NO donors towards early stage biofilms formed by type strains, or did not specify optimal treatment time which is crucial for the interpretation of data from young biofilms to distinguish between prevention and dispersal (Barraud et al 2009a ; Barnes et al 2013 ; Sadrearhami et al 2017 ; Duong et al 2014a ; Shen et al 2019 ; Duong et al 2014b ; Zhu et al 2018 ; Marvasi et al 2014 ). To this end, we systematically compared the optimal concentrations and treatment time of 7 NO donors for triggering biofilm dispersal using P. aeruginosa PAO1, including SNP, S-nitroso-glutathione (GSNO), S-nitroso-N-acetyl-DL-penicillamine (SNAP), 1-(hydroxy-NNO-azoxy)-L-proline (PROLI NONOate), 6-(2-hydroxy-1-methyl-2-nitrosohydrazino)-N-methyl-1-hexanamine (MAHMA NONOate), (Z)-1-[N-[3-aminopropyl]-N-[4-(3-aminopropylammonio)butyl]-amino]diazen-1-ium-1,2-diolate (Spermine NONOate) and diethylammonium (Z)-1-(N,N-diethylamino)diazen-1-ium-1,2-diolate (DEA-NONOate).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also recently shown that NO inhibits S. aureus virulence by disrupting intercellular communication between bacterial cells by targeting proteins involved in quorum sensing (46). Biofilm formation in P. aeruginosa is also affected by NO in a concentration dependent manner and the bacteria harbor NO-responsive regulators that modulate biofilm dispersal (54, 55).…”
Section: Introductionmentioning
confidence: 99%
“…While the exogenous addition of NO can disperse a significant portion of biofilms, the addition of NO generally does not disperse all of the biofilms(27). We have recently shown that the non-dispersing cells become insensitive to NO as a consequence of producing a flavohemoprotein capable of scavenging free NO signals(169).One of the most important reactions in which NO participates in biological systems are those with iron, where NO can bind to heme sensors, affect cytochromes or iron-sulfur clusters(170). Interestingly, iron has been shown to impact biofilm developmental processes, but the link between iron and NO inthe regulation of biofilms remains poorly understood.…”
mentioning
confidence: 99%